A glance at Berberis integerimma pharmacological effects and its active constituents - Mahmoudreza Moein; Zahra Sabahi; Hasti Salim (Shiraz University of Medical Sciences, 2020)
Berberis integerimma (family: Berberidaceae) is broadly used in the pharmacological studies as a rich source of bioactive compounds. Phytochemical investigations reveal that Berberis integerimma (B. integerimma) contains alkaloids derivates. Material and methods: this study introduced pharmacological effects of B. integerimma by reviewing the plant related study through available databases including Web of Science, Pub Med and Google Scholar. The present review attempts to give a short overview on the pharmacological studies and active compounds of B. integerimma with emphasis on some mechanisms of activities. Results: scientific evidence suggested the possible therapeutic properties of this plant on diseases such as diabetes, inflammation,free radicals associated diseases, seizure and cancer. Conclusion: In this review, we evaluated the most correlated original articles to determine the role of B. integerima on different medical conditions. This suggests a potential role of B. integrimma in the managing of disease; however more studies, especially pharmacokinetic and clinical trials, need to be considered to evaluate their efficiency or reveal its toxicity and side effects.